Study on Deterioration Characteristics of Low-Carbon Steel’s Mechanical Properties and Fracture Mechanism under Marine Engineering Environment - Lili Cao; Ming Li; Jiazhi Zhang; Gang Lin; Baichuan Gong; Xianbiao Mao; Lianying Zhang; Yan Li (Advances in Civil Engineering)
In order to study the mechanical properties of low-carbon steel under the coupling effect of the overall environment and the loads, the tensile mechanical test was carried out. The results indicated that, as the sea water concentration and tensile deterioration increased, both the mass-loss rate and surface roughness of the low-carbon steel gradually increased, and the yield strength, tensile strength, elongation, and section shrinkage decreased gradually. The mechanical parameters of the low-carbon steel were affected by the joint actions of the sea water concentration and tensile deterioration. The established mechanical model of low-carbon steel under the marine engineering environment shows that tensile deterioration had no effects on the fracture toughness, while the increase of sea water concentration could reduce the fracture toughness remarkably.